The shift from "e‐learning" to "learning": Invisible technology and the dropping of the "e". (18th February 2015) - Paiva, João; Morais, Carla; Costa, Luiza; Pinheiro, Ana
Abstract: Due to the generalization of electronically supported activities, we anticipate that, in the near future, the letter "e" in "e‐learning, " indicating the use of electronic media and information and communication technologies in education, will be dropped and that "e‐learning" will be referred to as simply "learning." This paper presents an attempt at understanding the causes of the name shift and at predicting its consequences. We offer a constructive reflection on how e‐learning has been looked upon and on what we foresee will happen in the future, drawing briefly on several areas of knowledge and on the experience of the authors as educators at university, teacher training and high school levels. Our effort has also resulted in greater awareness of the importance of social tools and of the relevance of the human factor in the learning process.